Work-Life Balance and Professional Development on Employee Performance - Basalamah, Indira; Andi Haerani, Muhammad Carda P, (YUME : Journal of Management, 2024)
Work-life balance and professional development are crucial factors influencing employee performance in modern organizations. Achieving a balance between work and personal life enhances employee well-being, reduces stress, and increases job satisfaction, which in turn improves productivity and engagement. Simultaneously, continuous professional development, such as training and skill enhancement, equips employees with the necessary competencies to adapt to changing business environments and technological advancements. This study explores the impact of work-life balance and professional development on employee performance, analyzing their interplay in fostering a motivated and high-performing workforce. Through a review of existing literature and empirical studies, the findings suggest that organizations that prioritize work-life balance initiatives and invest in professional growth opportunities experience higher levels of employee commitment, efficiency, and overall performance. The paper concludes with recommendations for HR strategies that integrate work-life balance policies and professional development programs to optimize employee output and organizational success. Keywords: Work-Life Balance, Professional Development, Employee Performance, Job Satisfaction, HR Strategies